Arabic complementary schools in England: language and Fundamental British Values. Issue 1 (2nd January 2020) - Szczepek Reed, Beatrice; Said, Fatma; Davies, Ian; Bengsch, Geraldine
ABSTRACT: Heritage language education is not included in the national curriculum in England, and therefore formal learning and teaching of heritage languages are primarily achieved through complementary schools, which are part-time, community-led and linked to various ethnic and national backgrounds. This study focuses on Arabic complementary schools and explores educational practices for teaching Arabic. The study also explores how pupils and teachers conceptualise, construct and manifest their linguistic and social identity, especially with regard to the context that is informed by the promotion of so-called Fundamental British Values (FBV). Observations are based on data from interviews with pupils, teachers and headteachers from three Arabic complementary schools across England. A qualitative analysis of the data reveals that the schools are strongly committed to tolerance and respect, which are part of the FBV; as well as to inclusivity and community cohesion. The analysis also shows that Arabic plays an important role in the construction of community and linguistic identities in the current political environment of suspicion.